Expression Analysis of SOCS Genes in Migraine - Ghafouri-Fard, Soudeh; Honarmand Tamizkar, Kasra; Sayad, Arezou; Taheri, Mohammad; Samadian, Mohammad (Frontiers in Molecular Neuroscience, 2021)
Migraine is a complex neurological condition affecting a large proportion of persons. Dysregulation of several immune-related transcripts has been noted in migraineurs suggesting an immune-based background for this condition. We measured expression levels suppressor of cytokine signaling (SOCS) genes in the venous blood of migraineurs compared with controls. SOCS1 was down-regulated in patients without aura compared with controls (Ratio of mean expression (RME)=0.08, P value<0.001). This pattern was also detected among female subgroups (RME=0.06, P value=0.010), but not among male subgroups (RME=0.22, P value=0.114). Expression of SOCS1 was significantly higher in patients with aura compared with those without aura (RME=5.89, P value=0.037). Meanwhile, expression of SOCS2 was lower in migraineurs with aura compared with controls (RME=0.03, P value<0.001). In addition, this gene was under-expressed in patients without aura compared with controls and in both sex based subgroups of this group of patients (RME=0.01, P value<0.001 for all comparisons). However, its expression was higher in male patients with aura compared with those without aura (P value<0.001). For SOCS3, we detected a lower level of expression in patients without aura compared with controls (RME=0.07, P value<0.001). However, expression of SOCS3 was higher in patients with aura compared with those without aura (RME=7.46, P value=0.001). SOCS5 was down-regulated in patients without aura compared with controls (RME=0.10, P value<0.001). Expression of this gene was also lower in patients with aura compared with controls (RME=0.03, P value<0.001), and in male patients of this group compared with controls (RME=0.03, P value=0.004). On the other hand, expression of SOCS5 was higher in male patients with aura compared with sex-matched patients without aura (RME=6.67, P value=0.001). SOCS2 levels could appropriately differentiate migraineurs from healthy subjects. The current study suggests the role of SOCS genes in the pathoetiology of migraine.